Syntheses of Biologically Active 3-[4-(4-Substituted amino-4-ylmethyl- 5-thione[1,3,4]oxadiazol-2-yl-methoxy)- phenyl]-2-phenyl-3H-quinazolin-4-ones - Havaldar, Freddy H.; Patil, Abhay R. (Asian Journal of Chemistry, 2010)
A number of Mannich base quinazoline derivatives possessing 1,3,4-oxadiazole ring have been synthesized by reacting 3-[4-(5-thione[1,3,4]-oxadiazol-2-yl-methoxy)-phenyl]-2-phenyl-3H-quinazolin-4-one (V) with different secondary amines and formaldehyde using N,N-dimethylformamide as the solvent to afford 3-[4-(4-substituted amino-4-yl-methyl-5-thione[1,3,4]oxadiazol-2-yl-methoxy)phenyl]-2-phenyl-3H-quinazolin-4-ones (VIa-d). The structures of the newly synthesized compounds have been established by analytical and spectral methods. The compounds have also been screened for their biological activity.